Impaired Oligodendrocyte Development Following Preterm Birth: Promoting GABAergic Action to Improve Outcomes - Julia C. Shaw; Julia C. Shaw; Gabrielle K. Crombie; Gabrielle K. Crombie; Hannah K. Palliser; Hannah K. Palliser; Jonathan J. Hirst; Jonathan J. Hirst (Frontiers Media S.A., 2021)
Preterm birth is associated with poor long-term neurodevelopmental and behavioral outcomes, even in the absence of obvious brain injury at the time of birth. In particular, behavioral disorders characterized by inattention, social difficulties and anxiety are common among children and adolescents who were born moderately to late preterm (32-37 weeks' gestation). Diffuse deficits in white matter microstructure are thought to play a role in these poor outcomes with evidence suggesting that a failure of oligodendrocytes to mature and myelinate axons is responsible. However, there remains a major knowledge gap over the mechanisms by which preterm birth interrupts normal oligodendrocyte development. In utero neurodevelopment occurs in an inhibitory-dominant environment due to the action of placentally derived neurosteroids on the GABAA receptor, thus promoting GABAergic inhibitory activity and maintaining the fetal behavioral state. Following preterm birth, and the subsequent premature exposure to the ex utero environment, this action of neurosteroids on GABAA receptors is greatly reduced. Coinciding with a reduction in GABAergic inhibition, the preterm neonatal brain is also exposed to ex utero environmental insults such as periods of hypoxia and excessive glucocorticoid concentrations. Together, these insults may increase levels of the excitatory neurotransmitter glutamate in the developing brain and result in a shift in the balance of inhibitory: excitatory activity toward excitatory. This review will outline the normal development of oligodendrocytes, how it is disrupted under excitation-dominated conditions and highlight how shifting the balance back toward an inhibitory-dominated environment may improve outcomes.